2020
DOI: 10.1021/acs.energyfuels.9b04357
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Simultaneous Measurement of O2 and CO Concentrations in the Exhaust Gas of a Methane/Air Flame Using Tunable Diode Laser Absorption Spectroscopy

Abstract: Oxygen (O2) and carbon monoxide (CO) are produced in combustion reactions and are important gas species, which are closely related to combustion efficiency and production of air pollutants. O2 generates thermal nitrogen oxide (NO x ) by reacting with nitrogen in the air at high temperatures, and the presence of excess O2 also affects the energy efficiency as a result of increasing exhaust heat energy. CO is generally well-known for being a toxic gas and is a crucial gas species produced by incomplete combustio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Matamba et al 8 reported the promotion effects of pressure on polycyclic aromatic hydrocarbons and H 2 formation during flash pyrolysis of palm kernel shell biomass using a pressurized entrained flow reactor. So et al 9 reported the simultaneous measurement of O 2 and CO concentrations in the exhaust gas of a methane/air flame using tunable diode laser absorption spectroscopy. The applications of carbon materials from coal and biomass for battery and energy conversion represented the recently increased research interests and are reflected by the papers below.…”
mentioning
confidence: 99%
“…Matamba et al 8 reported the promotion effects of pressure on polycyclic aromatic hydrocarbons and H 2 formation during flash pyrolysis of palm kernel shell biomass using a pressurized entrained flow reactor. So et al 9 reported the simultaneous measurement of O 2 and CO concentrations in the exhaust gas of a methane/air flame using tunable diode laser absorption spectroscopy. The applications of carbon materials from coal and biomass for battery and energy conversion represented the recently increased research interests and are reflected by the papers below.…”
mentioning
confidence: 99%